Gerência de energia em agrupamentos de servidores na Internet - Rodrigo Pereira Braga (2006)
Most of the servers currently on the Internet are actually distributed systems to improve scalability, however such cluster-based servers consume significant amounts of energy (which must include the cooling infrastructure). These costs can be reduced by adjusting the number of powered nodes based on the processing capacity needed to serve the load perceived as time varies, for example, reducing the number of powered machines as the load decreases. In this work we present a transparent architecture for enabling such power management. We applied this architecture to three different Internet services: a Webserver, a Search Engine and an Multi-tiered E-Commerce Server. Our results show that energy consumption may be reduced by as much as 30% in some cases,with little effect on performance perceived by the user.